2017
DOI: 10.1080/15548627.2017.1319039
|View full text |Cite
|
Sign up to set email alerts
|

w09, a novel autophagy enhancer, induces autophagy-dependent cell apoptosis via activation of the EGFR-mediated RAS-RAF1-MAP2K-MAPK1/3 pathway

Abstract: The EGFR (epidermal growth factor receptor) signaling pathway is frequently deregulated in many malignancies. Therefore, targeting the EGFR pathway is regarded as a promising strategy for anticancer drug discovery. Herein, we identified a 2-amino-nicotinonitrile compound (w09) as a novel autophagy enhancer, which potently induced macroautophagy/autophagy and consequent apoptosis in gastric cancer cells. Mechanistic studies revealed that EGFR-mediated activation of the RAS-RAF1-MAP2K-MAPK1/3 signaling pathway p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
63
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 59 publications
(64 citation statements)
references
References 69 publications
0
63
1
Order By: Relevance
“…This implies that upregulation of autophagy by inhibition of EGFR could augment cell death under stress. However, our recent work demonstrated that active EGFR‐mediated RAS/RAF1/MAP2K/MAPK1/3 signaling pathway could contribute to increase autophagy‐dependent apoptosis in gastric cancer cells . Fulda and Kögel also reported that Obatoclax enhanced breast carcinoma cell death induced by lapatinib through suppressing the EGFR/AKT/mTOR signaling and enhanced autophagy …”
Section: Egfr and Autophagy Process (Fig )mentioning
confidence: 94%
See 4 more Smart Citations
“…This implies that upregulation of autophagy by inhibition of EGFR could augment cell death under stress. However, our recent work demonstrated that active EGFR‐mediated RAS/RAF1/MAP2K/MAPK1/3 signaling pathway could contribute to increase autophagy‐dependent apoptosis in gastric cancer cells . Fulda and Kögel also reported that Obatoclax enhanced breast carcinoma cell death induced by lapatinib through suppressing the EGFR/AKT/mTOR signaling and enhanced autophagy …”
Section: Egfr and Autophagy Process (Fig )mentioning
confidence: 94%
“…Moreover, there is extensive cross‐talk between autophagy and other forms of cell death, such as apoptosis and necrosis . Therefore, the effect of autophagy on cell death may also depend on its cross‐talk with apoptotic and/or necrotic pathways …”
Section: Autophagy Autophagic Flux and Autophagic Cell Death (Acd)mentioning
confidence: 99%
See 3 more Smart Citations